The infamous Ratsos - LaReau, Kara (LaReau, Kara. Infamous Ratsos., 2016)
Rat brothers Louie and Ralphie Ratso try to prove they can be as rough and tough as their father in the Big City, but every time they try to show how tough they are, they end up accidentally doing good deeds instead.